Serbian Free Legal Aid Fiscal Impact Analysis : Volume, Costs, and Alternatives - World Bank (Washington, DC, 2014)
This report estimates the combined costs of providing primary and secondary free legal Aid (FLA) services in Serbia. Most estimates are for the combined costs of what has traditionally been considered secondary legal aid services, that is, for the total costs of legal advice, petition and representation for cases that reach the court docket. Separate aggregate estimates are also made for volume and costs for the traditional form of primary legal aid, as well as for its expanded definition (inclusive of drafting legal documents and motions). Still, the body of these cost estimates focus on the combined cost of primary (in its expanded form) and secondary legal aid, minus the cost of initial consultation and screening (the previous definition of primary legal aid). Due to the constitutional assignment of legal aid functions to Municipal Governments, to the degree possible, this report attempts to estimate legal aid case demands and case costs down to the municipal level as well as court levels. However, aggregate estimates are likely to be more accurate than individual municipal estimates.